The Correlation between Perceived Social Support with Suicide Ideation - Prima Kusumastuti; Innawati Jusup; Alifiati Fitrikasari; Titis Hadiati (Diponegoro International Medical Journal, 2021)
Background: Based on data from WHO in 2015, it shows that the death rate due to suicide in the world was recorded to have increased by 23.2% compared to 2009. Research in 2016 shows that the largest age range who experienced suicide was from 15-29 years. Many things are predicted to be a protective factor against suicide, including social support. Research on suicide protection factors is useful in preventing the increasing number of suicides.Objective: To analyze the correlation between perceived social support with suicidal ideationMethods: This research is a quantitative study with cross sectional design. Samples were taken from vocational school and academy in Semarang, who met the inclusion and exclusion criterias. The sample selection was carried out by the simple random sampling method. This research used the Indonesian version of the SSI (Scale of Suicide Ideation) and the MSPSS (Multidimentional Scale of Perceived Social Support) questionnaires.Results: It was found that the prevalence of high suicidal ideation score was 50.8% while the low suicidal ideation score was 49.2%. There was a significant correlation between suicidal ideation with perceived of family support (p = 0.002) and peer support (p = 0.050). Meanwhile, there was no significant correlation between the suicidal ideation and the support from significant others (p = 0.154). Conclusion: There was a correlation between perceived of family and peer support with suicidal ideation